2015
DOI: 10.1002/etc.3167
|View full text |Cite
|
Sign up to set email alerts
|

Arabian killifish (Aphanius dispar) embryos: A model organism for the risk assessment of the Arabian Gulf coastal waters

Abstract: Fish embryos are excellent models for studies aimed at understanding toxic mechanisms and indications of possible acute and chronic effects. For the past 3 yr, an Arabian killifish (Aphanius dispar) fish embryo test has been developed in the authors' laboratory as a routine ecotoxicological test that can be used to support risk assessment of potential contaminants in Arabian Gulf coastal waters. Tests were conducted with 3 reference toxicants (3,4-dichloroaniline [DCA], sodium dodecyl sulfate, and zinc sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…However, toxic and embryotoxic effects reported in fish for 3,4-DCA are observed at concentrations nearly one order of magnitude higher than those tested in the present study. For fish embryotoxicity assay, EC50 values are in the range of mg.L -1 (Zhu et al 2013;Saeed et al 2015), e.g., around 6 mg.L -1 in the zebrafish (Braunbeck & Lammer 2006). In crucian carp, Li et al (2003) showed that 3,4-DCA triggered necrosis and degenerative lesions in liver that could be due to oxidative stress and lipid peroxidation from the concentration of 0.2 mg.L -1 .…”
Section: Diuron Is More Toxic Than Its Studied Metabolitesmentioning
confidence: 99%
“…However, toxic and embryotoxic effects reported in fish for 3,4-DCA are observed at concentrations nearly one order of magnitude higher than those tested in the present study. For fish embryotoxicity assay, EC50 values are in the range of mg.L -1 (Zhu et al 2013;Saeed et al 2015), e.g., around 6 mg.L -1 in the zebrafish (Braunbeck & Lammer 2006). In crucian carp, Li et al (2003) showed that 3,4-DCA triggered necrosis and degenerative lesions in liver that could be due to oxidative stress and lipid peroxidation from the concentration of 0.2 mg.L -1 .…”
Section: Diuron Is More Toxic Than Its Studied Metabolitesmentioning
confidence: 99%
“…It is a secondary freshwater fish and is well known for its remarkable capacity to adapt to different ecological conditions (Teimori et al., ). Thus, it is generally an attractive model to be studied for different aspects including the understanding of ecological plasticity, evolutionary processes, environmental studies, histopathological changes and recently regeneration capacity (Ferrito et al., ; Iranmanesh & Motamedi, ; Motamedi, Shamsaldini, Teimori, & Askari Hesni, ; Parenti, ; Saeed, Al‐Naema, Butler, & Febbo, ; Teimori et al., ; Tigano et al., ; Wildekamp, Kücük, Ünlüsayin, & Neer, ; Zeinali & Motamedi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Beside this standard biological model, the members of killifishes (Cyprinodontiformes) have also been used successfully in different biological studies. Examples are Nothobranchius furzeri Jubb, 1971 for studies on aging (Genade et al, ; Terzibasi et al, ; Wendler et al, ) or Aphanius dispar (Rüppell, 1829) for the assessment of environmental pollution (Saeed, Al‐Naema, Butler, & Febbo, ).…”
Section: Introductionmentioning
confidence: 99%
“…They would be good candidates in order to eliminate mosquito larvae from the environments and consequently to remove the mosquito borne diseases such as dengue, and rift valley fever (Al‐Akel & Suliman, ). In addition, the embryo of Aphanius has been used as model in ecotoxicological tests for risk assessment of potential contaminants in coastal waters (Saeed et al, ). Also, the Mediterranean species of Aphanius (known as A. fasciatus ) has been used as excellent monitoring species for the analysis of environmental impact on the coastal Mediterranean regions (Kessabi et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation